TV KABEL DAN POLA PENDIDIKAN ANAK DI LOMBOK TIMUR - Muhammad Ridwan Markarma (Universitas Hamzanwadi, 2009)
The objective of the study was to asses the change of family education sistim, pre and post the presence of cable TV at the urban village Pancor the sub district Selong the district Lombok Timur, the model of family education: character building and spiritual education for the community in Bongki who use the cable TV, and to assess the effectiveness of the family education sistim applied. This was a case study employing the descriptive qualitative approach. The data resources in this research were theree families who were selected using the depth interviews and observation and then analyzed employing the descriptive qualitative technique. The result of the study unfolded that there was a contrast change of family education sistim pre and post the presence of cable TV in this very community. Prior to the presence of cable TV, the transformation processes of Islamic spiritual doctrines and cuktural values were handled by religion teachers at school, or the Koran recital teachers. In the spiritual education context, parents educated their children how to pray and to make the praying as an important part of their living. Beside that, the parents taught their children to recite the Koran in a good and correct way. The education sistim applied by the community in Pancor was categorized effective. This was evidently proven by the outputs of education; good and noble characters in life and solid act devotion as well as children’s proficiency in reciting the Koran. Keywords: cable TV, model of family education, descriptive qualitative approach